(untitled) (Journal of Medical & Health Sciences Review, 2025)
This study presents the fabrication and evaluation of nanostructured metal oxide-modified electrodes for the highly sensitive electrochemical detection of heavy metal ions in water. Zinc oxide (ZnO) nanorods, titanium dioxide (TiO₂) nanoparticles, and tin dioxide (SnO₂) nanostructures were synthesized via hydrothermal and sol-gel methods and characterized using XRD, SEM, BET, FTIR, and XPS. These analyses confirmed the successful formation of crystalline, high-surface- area, and mesoporous materials with abundant surface hydroxyl groups. The nanostructures were used to modify glassy carbon electrodes (GCEs), which were then assessed using electrochemical impedance spectroscopy (EIS) and differential pulse anodic stripping voltammetry (DPASV). The ZnO nanorod-modified GCE (ZnO/GCE) demonstrated superior performance, achieving the lowest detection limits of 0.4 ppb for Pb²⁺, 0.6 ppb for Cd²⁺, and 0.3 ppb for Hg²⁺, attributed to its optimal morphology and enhanced electron transfer kinetics. The sensors exhibited excellent selectivity, reproducibility (<5% RSD), and long- term stability (>90% response after 4 weeks). This work highlights the significant potential of simple, cost-effective metal oxide nanostructures, particularly ZnO nanorods, as high-performance platforms for on-site water quality monitoring.